Numerical analysis model for the instantaneous grinding temperature of face gears with a worm grinding wheel - WANG Chao; GUO Hui; RUAN Yuhang; RAN Xiaoping; ZHAO Ning (Jixie chuandong)
ObjectiveThe thermal distribution during the grinding of face gears using a worm grinding wheel is complex, with the heat being concentrated primarily on the surface layer of the wheel teeth, which can lead to thermal deformation and damage. In order to improve the situation, a numerical computational model for the instantaneous grinding temperature of face gears with a worm grinding wheel was established to investigate the distribution and variation patterns of the grinding temperature.MethodsFirstly, based on the geometric contact characteristics between the face gear and the worm grinding wheel during the grinding process, a quadratic surface was employed to approximate the instantaneous contact region and derive a calculation formula for the instantaneous grinding contact area. Secondly, the forces acting on individual abrasive grains during the grinding process were analyzed, taking into account factors such as the number of participating abrasive grains and their average grinding thickness, thereby obtaining the instantaneous tangential and normal forces. Subsequently, the generation and transfer of heat during the grinding process were examined, leading to the development of a numerical analysis model for the instantaneous grinding temperature of face gears with a worm grinding wheel. Finally, the proposed model’s computational accuracy was validated through the test of the grinding temperature.ResultsThe analysis results demonstrate that the instantaneous grinding temperature significantly increases from the inner diameter to the outer diameter at a fixed tooth height position. Moreover, at a constant tooth width position, the temperature gradually rises from the tooth tip to the tooth root, albeit with a small magnitude of variation. Furthermore, the instantaneous grinding temperature rises with increased grinding depth, feed rate, and wheel speed, with the grinding depth and wheel speed exhibiting more pronounced influences.